Evaluation of potential analgesic drugs using new models to study pain in dogs and cats - Niyom, Sirirat, author; Boscan, Pedro, advisor; Mama, Khursheed, committee member; Vader-Lindholm, Connie, committee member; Rezende, Marlis, committee member (Colorado State University. Libraries, 2013)
Pain remains an important health issue in both humans and animals. To improve the management of pain and understand the underlying mechanisms, animal models of pain have been generated over the past few decades. This dissertation presents two new models of acute pain developed to evaluate drug effects on nociceptive responses in cats and dogs. The first model determines the MAC sparing effect of an agent during visceral noxious stimulus of the ovary and ovarian ligament in the anesthetized cat. This technique was developed for dogs and modified subsequently to investigate the anesthetic sparing effect of different drugs in cats. The second method evaluates the efficacy of analgesic medications in conscious dogs using nociceptive threshold testing devices. One thermal and two mechanical nociceptive threshold testing devices were utilized to evaluate the antinociceptive effect of different drugs such as buprenorphine in dogs. Both models are promising to test the analgesic effect of different drugs. Maropitant, NK-1 antagonist, reduced significantly the anesthetic requirements during the ovary and ovarian ligament stimulation in cats. This indicates that maropitant may have the antinociceptive properties encouraging and supporting further investigation of this agent in clinical trials. Orotransmucosal buprenorphine increased thermal and mechanical nociceptive thresholds in dogs using the three testing devices. These findings show potential of the OTM route as an alternative administration of buprenorphine for pain treatment in dogs.
Keywords: animal models of acute pain; buprenorphine; cats; dogs; maropitant; nociceptive threshold